Ultrafast chiral separations for high throughput enantiopurity analysis. Issue 3 (22nd November 2016) - Barhate, Chandan L.; Joyce, Leo A.; Makarov, Alexey A.; Zawatzky, Kerstin; Bernardoni, Frank; Schafer, Wes A.; Armstrong, Daniel W.; Welch, Christopher J.; Regalado, Erik L.
Abstract : Ultrafast chiral chromatography enables high throughput enantiopurity analysis (over one thousand samples in an 8 h workday) for enantioselective synthesis investigations. Abstract : Recent developments in fast chromatographic enantioseparations now make high throughput analysis of enantiopurity on the order of a few seconds achievable. Nevertheless, routine chromatographic determinations of enantiopurity to support stereochemical investigations in pharmaceutical research and development, synthetic chemistry and bioanalysis are still typically performed on the 5–20 min timescale, with many practitioners believing that sub-minute enantioseparations are not representative of the molecules encountered in day to day research. In this study we develop ultrafast chromatographic enantioseparations for a variety of pharmaceutically-related drugs and intermediates, showing that sub-minute resolutions are now possible in the vast majority of cases by both supercritical fluid chromatography (SFC) and reversed phase liquid chromatography (RP-LC). Examples are provided illustrating how such methods can be routinely developed and used for ultrafast high throughput analysis to support enantioselective synthesis investigations.